Advance in Significant Wave Height Prediction: A Comprehensive Survey - Jinyuan Mo; Xianghan Wang; Shengjun Huang; Rui Wang (Complex System Modeling and Simulation)
The significant wave height prediction holds critical value for marine energy development, coastal infrastructure planning, and ensuring safety in maritime operations. The precision of such predictions carries substantial theoretical and practical weight. This survey delivers an exhaustive evaluation and integration of the latest studies and advances in the domain of significant wave height prediction, serving as a methodical guidepost for academicians. The study introduces an all-encompassing predictive framework for significant wave height, which not only integrates diverse established forecasting techniques but also paves the way for novel research trajectories and creative breakthroughs. The framework is structured into four principal layers, i.e., feature selection, basic prediction, data decomposition, and parameter optimization. The ensuing sections meticulously dissect the methodologies within these strata, elucidating their core concepts, distinctive features, merits, and constraints, and their applicability to significant wave height prediction. To wrap up, the study delves into fresh research inquiries and avenues pertinent to the discipline, thereby broadening the comprehension of significant wave height prediction. In essence, this scholarly article imparts critical knowledge beneficial to the realm of marine technology.